2017
DOI: 10.14299/ijser.2017.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Angiogenesis by Anthocyanin-Rich Extracts of Hibiscus sabdariffa

Abstract: Abnormal vessel formations contribute to the progression of specific angiogenic diseases including age-related macular degeneration. Adequate vessel growth and maintenance represent the coordinated process of endothelial cell proliferation, matrix remodeling, and differentiation. However, the molecular mechanism of the proper balance between angiogenic activators and inhibitors remains elusive. In addition, quantitative analysis of vessel formation has been challenging due to complex angiogenic morphology. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…The investigation for the anticancer potential of the Hibiscus sabdariffa plant began roughly in the last decade that emerged with encouraging results [63][64][65][66][67][68][69]. Both crude extracts and pure compounds of the plant were reported to induce chemoprevention, selective cytotoxicity, cell cycle arrest, apoptosis, autophagy and antimetastatis effects in various types of human cancer cells.…”
Section: Anticancer Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…The investigation for the anticancer potential of the Hibiscus sabdariffa plant began roughly in the last decade that emerged with encouraging results [63][64][65][66][67][68][69]. Both crude extracts and pure compounds of the plant were reported to induce chemoprevention, selective cytotoxicity, cell cycle arrest, apoptosis, autophagy and antimetastatis effects in various types of human cancer cells.…”
Section: Anticancer Activitymentioning
confidence: 99%
“…Several researchers reported the cytotoxic, antimutagenic, antimetastatic, antiproliferative, apoptotic antiangiogenic activity of Hibiscus sabdariffa both in human and animal cancer cells. This activity of Hibiscus sabdariffa is due to the presence of polyphenols in it, which attributes towards its antioxidant and anticarcinogenic activities [64][65][66][67][68][69]. The anticancer potential of Hibiscus sabdariffa leaves extracts (methanol, ethanol, ethyl acetate and chloroform) on hepatocellular carcinoma cell line Hep 3B was tested and methanolic extract showed a greater cytotoxic effect when compared with others [70].…”
Section: Anticancer Activitymentioning
confidence: 99%
“…According to a study reported by Joshua et al 75 , angiogenic parameters like extremities, nodes, junctions, master junction, master segments, master segment length, meshes, total mesh area, number of segments, branches, number of isolates segments, total length, total branching length, total segments length, total branches length, total isolated branches length, branching interval, total segments length /branches, mesh index, master segments length /master segments and mean mesh size could be successfully used to study the inhibition of angiogenesis in a chick embryo using an Angiogenic Analyzer software. These parameters were all used to show 50-60% inhibition of blood vessel formation in the sample where the angiogenesis inhibitor was tested.…”
Section: Discussionmentioning
confidence: 99%
“…HS inhibits angiogenesis and, therefore, can be helpful in treating angiogenesis-related diseases, including hypertension. 37 Sour tea induces Pharmaceutical Sciences (Indexed in ISI and Scopus) https://ps.tbzmed.ac.ir apoptosis in human gastric carcinoma cells through the p38 MAPK/FasL cascade pathway and p53 phosphorylation. In other words, HS extract acts as an apoptosis inducer in human gastric carcinoma (AGS) cells, and these discoveries are promising perspectives in human gastric cancer treatment.…”
Section: Sour Tea In Traditional Medicinementioning
confidence: 99%